Designing interactive Web sites / James L. Mohler and Jon M. Duff - Mohler, James L (Delmar/Thomson Learning, 1999)
This comprehensive book provides an in-depth look at the fundamentals of effective web design and site construction. The novice web designer learns the process of creating an interactive web site step by step, using real-world examples along the way. Users discover the fundamentals of web site coding without the use of any software specific packages. Advanced topics such as the construction of tables and JavaScript help the experienced designer create an effective site. The book teaches how other authoring programs relate to web design, as well as offering hints, tips, and tricks. The logical format and easy-to-read writing make this a perfect desktop reference.